Nickel-plated steel plate for battery shell and manufacturing method of nickel-plated steel plate
By forming a nickel iron diffusion layer and a nickel-cobalt alloy layer on the nickel-plated steel strip, the problems of poor bonding strength and insufficient corrosion resistance of the substrate and plating layer are solved, and the low internal resistance and high corrosion resistance of the nickel-plated steel plate are achieved. Suitable for power battery case.
Patent Information
- Application Number
- CN202310789089.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2024-12-31
AI Technical Summary
During the electroplating process, the existing nickel-plated steel strips have poor bonding power to the substrate and the coating, which is prone to denitriding of the coating. Excessive internal resistance affects the battery circulation performance, poor corrosion resistance and stability, and affects the battery service life.
The nickel-plated steel plate adopts a multi-layer structure, including a nickel-iron diffusion layer, a nickel-cobalt alloy layer on the upper and lower surfaces of the steel substrate. The first plating layer is 1.0-5.0 μm thick, the second plating layer is 3.0-6.0 μm thick, and the cobalt mass The fractions are 0.5-5.0% and 1.0-10.0%, respectively. The nickel-iron diffusion layer is formed by the nickel layer and the steel matrix to ensure the adhesion of the coating layer, and the low resistivity and high hardness of the nickel-cobalt alloy layer are used to improve corrosion resistance.
It achieves good adhesion, low internal resistance and high corrosion resistance of nickel-plated steel plates, and is suitable for power battery housings, improving the service life and processing performance of the battery.
Smart Images

Figure CN119221057A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of steel plates and manufacturing methods, and in particular to a nickel-plated steel plate for battery shells and a manufacturing method thereof. Background Art
[0002] China is a major producer and consumer of new energy batteries. Research and development of new energy batteries promotes the healthy development of the new energy industry and plays a vital social role. Nickel-plated steel strip is gaining increasing attention as a preferred material for new energy battery casings. There is a pressing need for nickel-plated steel casings that offer low cost, high corrosion resistance, excellent processability, and reliability.
[0003] Chinese patent publication CN110462102A, titled "Surface-treated metal plate, battery container, and battery," discloses a surface-treated metal plate. Due to the formation of a nickel-cobalt binary alloy layer with a specific oxide film on the metal plate, this coated steel plate prevents surface discoloration even during long-term storage and, when used as a battery container, improves battery life.
[0004] A Chinese patent document with publication number CN110079841A, titled "A Battery Steel Strip and Its Preparation Method," discloses a battery steel strip and its preparation method. By forming a dense semi-bright Ni-Co coating and a full-bright Ni-Co coating on the steel strip, the problem of poor adhesion between the steel strip substrate and the coating can be solved.
[0005] Chinese patent publication CN111699567A, entitled "Surface-treated steel sheet for battery containers and method for manufacturing surface-treated steel sheet for battery containers," discloses a surface-treated steel sheet. This invention ensures plating adhesion by forming a Ni-Fe alloy layer of appropriate thickness on the steel substrate side of the plating layer, and inhibits plating breakage by forming a hard Ni-Co-Fe layer on top of the Ni-Fe layer. As a result, the steel sheet has the advantages of maintaining battery life, being less prone to leakage, and having excellent workability.
[0006] The Chinese patent document with publication number CN105463540A, entitled "A stainless steel strip coated with nickel-cobalt / nickel / nickel-phosphorus multilayer film for battery shells and its preparation method", discloses a stainless steel strip coated with nickel-cobalt / nickel / nickel-phosphorus multilayer film for battery shells and its preparation method. The stainless steel strip consists of a stainless steel strip base and a nickel-cobalt / nickel / nickel-phosphorus multilayer film coated on one surface. The multilayer film stainless steel strip has excellent corrosion resistance and stamping performance.
[0007] The above patented technology discloses a method for preparing a steel strip with a nickel-cobalt alloy coating. However, the battery steel shell produced by the steel strip produced by a single nickel plating method in the electroplating process has the following problems: (1) The bonding force between the substrate and the coating is not ideal, and the coating is prone to nickel de-nickeling; (2) During the battery application process, the nickel-plated battery steel shell has excessive internal resistance, which affects the battery cycle performance; (3) The corrosion resistance and stability of the battery steel shell are poor during use, and the steel shell is easily corroded, thereby affecting the service life of the battery.
[0008] In view of this, it is necessary to provide a new method for preparing nickel-cobalt alloy-plated steel strip to overcome the above defects. Summary of the Invention
[0009] In order to solve the above technical problems, the first aspect of the present invention provides a nickel-plated steel plate, comprising a steel substrate and a first coating layer and a second coating layer respectively located on the upper surface and the lower surface of the steel substrate; the first coating layer and the second coating layer both comprise a nickel-iron diffusion layer, a nickel layer, and a nickel-cobalt alloy layer sequentially formed on the surface of the steel substrate;
[0010] wherein the thickness of the first coating layer is d1 = 1.0 to 5.0 μm, the thickness of the second coating layer is d2 = 3.0 to 6.0 μm, and d2>d1; and
[0011] On the surface of the first coating layer, the mass fraction of cobalt c1 is 0.5-5.0%; on the surface of the second coating layer, the mass fraction of cobalt c2 is 1.0-10.0%.
[0012] The present invention forms a multilayer structure coating including a nickel-iron diffusion layer, a nickel layer and a nickel-cobalt alloy layer on the surface of a steel substrate. The nickel-iron diffusion layer is formed between the nickel layer and the steel substrate to ensure that the coating has good adhesion. At the same time, the low resistivity, high hardness, good corrosion resistance and wear resistance of the nickel-cobalt alloy layer are utilized to make the nickel-plated steel plate have low internal resistance and high corrosion resistance, and have good processing performance, so that the nickel-plated steel plate of the present invention is suitable for use as power battery shell steel.
[0013] Preferably, the contents of each element in the first coating layer and the second coating layer are respectively: Ni: 50.0-95.0 wt.%, Co: 0.5-10.0 wt.%, Fe: 1.0-5.0 wt.%.
[0014] Preferably, the surface resistance of the nickel-plated steel plate is 80-120 mΩ.
[0015] Preferably, when the nickel-plated steel plate is placed in a sodium chloride solution with a mass fraction of 3.5%,
[0016] The immersion potential U1 of the first coating surface is -0.33 to -0.10 V, and the immersion potential U2 of the second coating surface is -0.32 to -0.10 V; and / or,
[0017] The corrosion potential of the first coating surface is u1 = -0.44 to -0.15 V, and the corrosion potential of the second coating surface is u2 = -0.42 to -0.20 V.
[0018] Preferably, the steel matrix of the nickel-plated steel plate of the present invention has the following composition in mass percentage: C: 0.02-0.065%, 0<Si≤0.03%, Mn: 0.1-0.32%, 0<S≤0.01%, Cu: 0.005-0.03%, Ni: 0.005%-0.035%, Cr: 0.015-0.065%, 0<Ti≤0.002%; the balance is Fe and unavoidable impurities.
[0019] A second aspect of the present invention provides a battery case formed from the above nickel-plated steel sheet. When in use, the first plating layer is exposed to the electrolyte of the battery, that is, the first plating layer is on the inner side of the battery case.
[0020] The third aspect of the present invention provides a method for manufacturing the above-mentioned nickel-plated steel plate, comprising: plating nickel and nickel-cobalt alloy on the upper and lower surfaces of a steel substrate in sequence to obtain a multi-layer steel strip, and then continuously annealing the multi-layer steel strip to form a nickel-plated steel plate.
[0021] Preferably, a Watt bath solution is used for nickel plating, and the Watt bath solution contains: 250-380 g / L of nickel sulfate (NiSO4·7H2O), 30-60 g / L of nickel chloride (NiCl2·6H2O), and 20-60 g / L of boric acid (H3BO3); more preferably, the pH of the Watt bath solution is 3.0-5.0, and the bath temperature is 40-65°C.
[0022] Preferably, the plating solution used for nickel-cobalt alloy plating contains: nickel sulfate (NiSO4·7H2O) 200-350 g / L, nickel chloride (NiCl2·6H2O) 35-60 g / L, boric acid (H3BO3) 35-45 g / L, cobalt sulfate (CoSO4·6H2O) 1-20 g / L and additives 0.05-0.15 g / L.
[0023] Preferably, the nickel plating current density a1 used to form the first plating layer is 1-5A / dm 2 , the current density of nickel-cobalt alloy plating is b1=3~10A / dm 2 ; The nickel plating current density a2 = 3-8A / dm 2 , the current density of nickel-cobalt alloy plating is b2 = 5 ~ 15A / dm 2 ; and a2>a1, b2>b1.
[0024] Preferably, a pulse current is used during nickel plating, and the duty ratio is 1:10-1:15; and a rectangular wave pulse current is used during nickel-cobalt alloy plating, and the duty ratio is 1:3-1:10.
[0025] Preferably, during continuous annealing, the soaking temperature is 600-800° C., preferably 680-750° C., and the soaking time is 10-300 s, preferably 30-200 s. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic structural diagram of a cross section of a nickel-plated steel plate according to the present invention;
[0027] Figure 2 Shown is an electroplating waveform diagram used in the nickel plating process of the present invention;
[0028] Figure 3 The electroplating waveform diagram used in the nickel-cobalt alloy plating process of the present invention is shown. DETAILED DESCRIPTION
[0029] The embodiments of the present invention are described in detail below with reference to the examples, wherein, unless otherwise specified, all percentages are by mass.
[0030] 1. Nickel-plated steel plate
[0031] The nickel-plated steel sheet of the present invention comprises a steel substrate, a nickel layer and a nickel-cobalt alloy layer sequentially plated on the surface of the steel substrate, and an iron-nickel diffusion layer located between the steel substrate and the nickel layer. The nickel-plated steel sheet is obtained by electroplating the upper and lower surfaces of the steel substrate and then performing a heat treatment. The nickel-plated steel sheet comprises a steel substrate, and a first and a second plating layer located on the upper and lower surfaces of the steel substrate, respectively. During the heat treatment, diffusion occurs at the interface between the steel substrate and the nickel layer plated thereon, forming an iron-nickel diffusion layer.
[0032] 2. Steel matrix composition
[0033] The steel substrate of the present invention is a cold-rolled thin plate. The composition of the cold-rolled plate used as the nickel-plated steel plate is not particularly limited. Typically, cold-rolled steel strip with a yield strength of 200 MPa or greater, a tensile strength of 300 MPa or greater, and an elongation of 30% or greater is selected. Preferably, the mass percentages of the elements in the steel substrate are as follows: C: 0.02-0.065%, 0 < Si ≤ 0.03%, Mn: 0.1-0.32%, 0 < S ≤ 0.01%, Cu: 0.005-0.03%, Ni: 0.005%-0.035%, Cr: 0.015-0.065%, 0 < Ti ≤ 0.002%; the remainder is Fe and unavoidable impurities.
[0034] The design principles of the chemical composition of the steel matrix are explained below.
[0035] Carbon (C) is the most effective and inexpensive strengthening element in steel. It increases the strength of steel, enhancing the strength of power battery casings and improving the pressure resistance of steel casings. However, high carbon content is detrimental to toughness. Considering the balance between strength and toughness in steel, the upper limit of the C content in this invention is 0.065%, and the lower limit is 0.02%.
[0036] Si: Si is a ferrite solid-solution strengthening element. Properly adding Si can enhance the strength of battery cases punched from steel sheets, improving their pressure resistance. However, excessive Si addition can degrade the steel's hot workability and weldability. The upper limit of Si content in this invention is 0.03%.
[0037] Mn: Mn exists primarily in a solid solution state in steel, where it combines with carbon to enhance the strength of the steel sheet. However, excessive Mn content can reduce the plastic strain ratio of the steel sheet after annealing, impairing the isotropy of the steel for deep-drawn battery cases and hindering their formability. Therefore, the upper limit of the Mn content in the present invention is 0.32%, and the lower limit is 0.1%.
[0038] S: Adding an appropriate amount of S to steel promotes the formation of a Cu2S passivation film on the steel surface, thereby inhibiting both anodic and cathodic electrochemical reactions and improving the corrosion resistance of the steel plate. However, excessive S content in steel can easily cause centerline segregation in the ingot, leading to hot brittleness and adversely affecting the steel's formability. Therefore, in the present invention, the S content is controlled to below 0.01%.
[0039] Ni and Cu: Ni and Cu promote the formation of low-temperature transformation phases, increasing steel strength. However, excessive addition of these elements saturates the strength-enhancing effect. Considering production costs, the present invention limits the content of Cu to 0.005-0.030% and Ni to 0.005-0.035%.
[0040] Cr: Adding Cr to steel improves its strength while also preventing surface damage during battery case stamping, which can degrade the case's corrosion resistance. However, excessive Cr content in steel can lead to the formation of a dense Cr oxide film on the substrate surface, impairing the adhesion of subsequent coatings. To balance the corrosion resistance of the case with the adhesion of the coating, the present invention uses a Cr content of 0.015-0.065%.
[0041] Ti: Ti exists in steel primarily as precipitates such as TiN and TiC, hindering grain growth and preventing grain coarsening. Adding a small amount to steel can reduce anisotropy and increase strength. Considering production costs, the upper limit of Ti content in this invention is 0.002%.
[0042] In the present invention, elements such as P, B, Nb, and N may be added to the substrate as needed.
[0043] 3. Nickel-plated steel plate composition
[0044] The nickel-plated steel sheet of the present invention has a first plating layer and a second plating layer respectively located on the upper and lower surfaces of the steel substrate. The thickness of the first plating layer is d1 = 1.0 to 5.0 μm, the thickness of the second plating layer is d2 = 3.0 to 6.0 μm, and d2> d1. The plating layers with a multilayer structure formed on the upper and lower surfaces of the steel substrate differ in thickness. Since the first plating layer directly contacts the electrolyte when the nickel-plated steel sheet of the present invention is made into a battery shell, and since the battery does not contain water or oxygen inside when in use, the corrosion resistance requirements are lower, so a thicker plating layer is not required. Figure 1 Schematic diagram of the structure of the cross section of the nickel-plated steel plate of the present invention.
[0045] In the present invention, during the continuous annealing process, element diffusion occurs at the interface between the steel substrate and the nickel layer coated thereon, causing the Ni in the nickel layer to diffuse into the steel substrate, and the elements (primarily Fe) in the steel substrate to diffuse into the nickel layer, thereby forming an iron-nickel diffusion layer between the steel substrate and the nickel layer. Therefore, when determining the thickness of the first coating, the position where the Ni content in the steel substrate reaches 1.0 wt.% is used as the boundary, and the distance from this boundary to the surface of the nickel-cobalt layer of the first coating is defined as the thickness of the first coating. The thickness of the second coating is determined in the same manner as the first coating.
[0046] In addition, on the surface of the first coating, the mass fraction of cobalt c1 = 0.5-5.0%; on the surface of the second coating, the mass fraction of cobalt c2 = 1.0-10.0%. The Co content on the coating surface should not be too low. If the Co content is insufficient, the low internal resistance of the diffusion layer cannot be obtained. In the present invention, the lower limit of the Co content on the coating surface is 0.5%, preferably 1.0%. At the same time, the Co content should not be too high. Too much Co cannot be dissolved in the plating solution, which will cause unnecessary cost waste. Generally, the upper limit of the Co content on the coating surface is 10.0%, preferably 8.0%. The function of Co is similar to that of Ni, and it has air corrosion resistance. However, when the battery is in use, the interior does not contain water or oxygen. Therefore, the first coating containing less Co can be used as the inner side of the battery shell.
[0047] The chemical compositions of the first and second coatings of the present invention each satisfy the following: Ni: 50.0-95.0 wt.%, Co: 0.5-10.0 wt.%, and Fe: 1.0-5.0 wt.%. During heat treatment to form a diffusion layer, the Fe in the steel substrate diffuses into the nickel-plated layer. To obtain a coating with good adhesion, the present invention sets the lower limit of the Fe content in the coating to 1.0%, preferably 2.0%, based on the total weight of the chemical composition of the coating. The more complete the element diffusion, the better the adhesion of the coating. However, if the Fe content in the coating is too high, the bonding strength between the coating and the steel substrate will not be significantly improved. Therefore, for manufacturing process cost considerations, the present invention sets the upper limit of the Fe content in the coating to 5.0 wt.%, preferably 4.0 wt.%, based on the total weight of the chemical composition of the coating.
[0048] The surface resistance of the nickel-plated steel plate of the present invention is 80-120 mΩ, preferably 80-100 mΩ. Compared with a steel plate having a coating containing only Fe and Ni (a steel substrate is only nickel-plated and then heat-treated), the internal resistance of the iron-nickel steel plate of the present invention is reduced by 10-30 mΩ, and its conductive performance is effectively improved.
[0049] When the nickel-plated steel plate of the present invention is placed in a sodium chloride solution with a mass fraction of 3.5%,
[0050] The immersion potential U1 of the first coating surface is -0.33 to -0.10 V, and the immersion potential U2 of the second coating surface is -0.32 to -0.10 V; and / or,
[0051] The corrosion potential of the first coating surface is u1 = -0.44 to -0.15 V, and the corrosion potential of the second coating surface is u2 = -0.42 to -0.20 V.
[0052] After a detailed study of the electrochemical corrosion behavior of the nickel-plated steel sheet with a multilayer coating according to the present invention, the inventors found that the coating can effectively inhibit the occurrence of electrochemical corrosion on the surface of the steel sheet, providing the steel sheet with excellent corrosion resistance. Specifically, in a 3.5% sodium chloride solution, the immersion potential of the first coating surface of the present invention increased by +0.15 to +0.35V, and the immersion potential of the second coating surface increased by +0.05 to +0.3V compared to the uncoated steel sheet. In addition, in a 3.5% sodium chloride solution, the corrosion potential of the first coating surface of the present invention increased by +0.25 to +0.3V, and the corrosion potential of the second coating surface increased by +0.2 to +0.25V compared to the uncoated steel sheet.
[0053] By adopting the technical solution of the present invention, a nickel-plated steel plate with a multi-layer structure is formed on the surface of a steel substrate, which can make the steel plate have lower internal resistance and higher corrosion resistance, making the nickel-plated steel plate suitable for use as a power battery shell, and has very considerable application prospects.
[0054] The nickel-plated steel sheets of Examples 1-16 of the present invention were prepared by sequentially performing the following steps:
[0055] 1) Pretreatment: Prior to the electroplating process, the steel substrate (cold-rolled steel strip) requires pretreatment. This pretreatment includes four steps: chemical degreasing, electrolytic degreasing, cleaning, and activation. Table 1 shows the chemical composition of the selected steel substrates. The present invention does not specifically limit the manufacturing method of the cold-rolled steel strip serving as the steel substrate; for example, the method disclosed in CN114107833A can be used.
[0056] Specifically, the cleaning system used for chemical degreasing contains: 50±10g / L NaOH, 40±10g / L Na2CO3, 40±10g / L Na3PO4, and 0.5mL / L detergent. During degreasing, the cleaning temperature is maintained at 65±5°C. The steel substrate is immersed in the chemical degreasing agent for 20-60 minutes. The surface oil is then scrubbed with a brush to achieve a degreasing level of 90-95%.
[0057] The cleaning system used for electrolytic degreasing contains: 50±10g / L NaOH, 40±10g / L Na2CO3, 40±10g / L Na3PO4, and 0.5mL / L detergent (commercial detergent similar to the chemical degreasing step is used). During degreasing, the cleaning temperature is maintained at 65±5℃ and the current density is maintained at 5A / dm 2 Connect an external power supply, the anode is the base steel plate, the cathode is the stainless steel plate or titanium alloy plate, and after about 30s to 60s of power on, the cathode and anode are exchanged, and this is repeated more than 3 times to remove about 5% to 10% of the remaining oil in the chemical oil.
[0058] Cleaning: After chemical degreasing and electrolytic degreasing, the steel substrate is first cleaned with hot water (50±5℃) once, and then cleaned twice with room temperature pure water.
[0059] Activation: The cleaned steel substrate is activated with 50-80 mL / L H2SO4. The Baume degree of the activation solution is 7-12°Bé at room temperature. The temperature during activation can be kept at room temperature. After the activation process is completed, it is washed twice with room temperature pure water.
[0060] Unless otherwise specified, all solutions in the present invention are aqueous solutions.
[0061] 2) Nickel plating: The pretreated steel substrate is immersed in a plating bath for electroplating nickel.
[0062] The plating bath used for electroplating nickel can be any commonly used plating bath in existing nickel plating processes, such as a Watts bath, an aminosulfonic acid bath, a borofluoride bath, and a chloride bath. In the embodiments of the present invention, the plating bath used in the nickel plating process is a semi-bright nickel or dark nickel formula that does not contain sulfur. Because bright nickel plating layers containing sulfur are prone to becoming hot brittle after alloying heat treatment, they can cause severe cracking in the plating layer of battery cases made of steel after stamping, resulting in deterioration of corrosion resistance. Therefore, they are not used in the present invention.
[0063] When nickel plating, Cl in the plating bath - The lower limit of the content is 16 g / L, preferably 20 g / L, more preferably 25 g / L, and the upper limit is 30 g / L; Ni 2+ The lower limit of the content is 60g / L, preferably 95g / L. Considering the solubility of nickel chloride in water, the plating bath Ni 2+ The upper limit of the content is 125g / L, preferably 100g / L. 2- The lower limit of the content is 90 g / L, and the upper limit is 140 g / L, preferably 120 g / L. The lower limit of the borate content is 20 g / L, preferably 35 g / L, and the upper limit is 60 g / L, preferably 50 g / L. The pH of the plating bath is preferably 2.5-6.5, more preferably 3.0-5.0. If the pH of the plating bath is too low, hydrogen evolution reaction is likely to occur, so the lower limit of the plating bath pH is 2.5, preferably 3.0. If the pH is too high, coating burns are likely to occur, so the upper limit of the plating bath pH is 6.5, preferably 5.0.
[0064] The plating bath temperature is preferably 40-65° C., more preferably 50-60° C. If the plating bath temperature is too low, the current efficiency may decrease and the stress may become relatively low. If the plating bath temperature is too high, the anode substrate may be dissolved.
[0065] In the embodiment of the present invention, it is preferred to use a Watt bath for nickel plating. The nickel plating current density a1 used to form the first plating layer is 1-5 A / dm 2 The nickel plating current density a2 = 3-8A / dm2 is used to form the second plating layer. 2 , and a2>a1. Too low current density will reduce productivity, and too high current density may cause current efficiency to decrease and plating burn. The inventors have found in experiments that when the current density is too low, the production efficiency will be reduced, and when the current density is too high, there is a possibility of causing current efficiency to decrease and plating burn. Therefore, in the process of forming the nickel layer, the current density is preferably 3A / dm 2 Above, 6A / dm 2 the following.
[0066] Preferably, a pulse current is used during nickel plating, and the duty ratio (the ratio of the on-time to the total time in one cycle) is 1:10-1:15, more preferably 1:12. Figure 2 The waveform diagram of the rectangular wave pulse current used in nickel plating of the present invention is shown.
[0067] Table 2 shows the specific nickel plating processes used in the examples and comparative examples, wherein comparative example 6 is not nickel plated.
[0068] 3) Nickel-cobalt alloy plating: The steel sheet obtained after nickel plating in step 2) is cleaned and then electroplated with nickel-cobalt alloy in a plating bath.
[0069] The plating bath formula used for electroplating nickel-cobalt alloy includes: nickel sulfate (NiSO4·7H2O) 200-350g / L, nickel chloride (NiCl2·6H2O) 35-60g / L, boric acid (H3BO3) 35-45g / L, cobalt sulfate (CoSO4·6H2O) 1-20g / L, and additives (such as sulfur-free component additives) 0.05-0.15g / L.
[0070] Preferably, the pH of the plating bath is 3.5-4.0. The pH of the plating bath should not be too high or too low. If the pH of the plating bath is too low, the steel plate may be easily dissolved. If the pH of the plating bath is too high, the coating may be easily burned.
[0071] Preferably, the plating solution temperature is 45-65° C. The plating solution temperature should not be too high or too low. If the plating solution temperature is too low, the current efficiency may be reduced and the stress may be relatively low. If the plating solution temperature is too high, the anode substrate may be dissolved.
[0072] The nickel-cobalt alloy plating current density b1 used to form the first plating layer is 3 to 10 A / dm 2 The nickel-cobalt alloy current density b2 used to form the second coating is 5-15A / dm 2 , and b2>b1. The inventors have found that too low a current density will reduce production efficiency, and too high a current density may cause a decrease in current efficiency and the possibility of coating burns. Therefore, the lower limit of the average current density for nickel-cobalt alloy plating is preferably 4A / dm 2 , the upper limit is preferably 12A / dm 2 .
[0073] When plating nickel-cobalt alloy, a rectangular wave pulse current is used, and the duty ratio is 1:3-1:10, preferably 1:5. That is, the duty ratio is 1:5 within one waveform cycle. Figure 3 The waveform of the rectangular wave pulse current used in the nickel-cobalt alloy plating of the present invention is shown.
[0074] Table 3 shows the specific nickel-cobalt plating alloys and continuous annealing processes used in the examples and comparative examples, wherein comparative example 5 is not nickel-cobalt plated.
[0075] 4) Cleaning and drying: After the nickel-cobalt alloy plating process, the steel plate is first cleaned 3 times with pure water at room temperature, then cleaned once with hot water (50±5℃) and then dried.
[0076] 5) Continuous Annealing: The steel sheet with the multi-layered coating is alloyed using a continuous annealing process, with the annealing soaking temperature controlled to 600-800°C, preferably 680-750°C, and the soaking time controlled to 10-300 seconds, preferably 30-200 seconds. After the annealing and alloying treatment, a multi-layered alloy coating is formed on the surface of the steel substrate, including a nickel-iron diffusion layer between the substrate and the nickel layer.
[0077] Continuous annealing is mainly to eliminate various defects inside the crystals and anisotropy in mechanical properties generated during the cold rolling of the steel plate. If the annealing temperature is too low, the yield strength of the steel increases, the elongation decreases, and the stamping workability deteriorates. The lower limit of the annealing temperature in the present invention is 600°C, preferably 650°C, and more preferably 680°C. However, if the annealing temperature is too high, the strength of the steel decreases, and the plane anisotropy (expressed by the Δr value) increases, affecting the use of the battery shell. Therefore, the upper limit of the annealing temperature is 800°C, preferably 750°C. During the annealing process, the size of the grains changes with time. Controlling the appropriate annealing time means controlling the size of the grains. In addition, the annealing time also affects the degree of alloying of the nickel-iron diffusion layer. Generally, the longer the annealing time, the higher the degree of alloying.
[0078] The nickel-plated steel plate formed through the above steps was characterized and tested for performance, and the results are recorded in Table 4. The test methods are as follows.
[0079] Certain specific process parameters of electroplating in Comparative Examples 1-4 are not within the scope defined by the present invention. The surface of Comparative Example 5 is only plated with nickel, and the surface of Comparative Example 6 is only plated with nickel-cobalt alloy.
[0080] Performance Testing
[0081] The Co, Ni, and Fe contents on the coating surface are determined as follows: a 10 mm x 10 mm sample is punched out from the surface of the nickel-cobalt alloy-plated steel plate that has undergone the annealing and alloying steps described above. The concentrations of Co, Fe, and Ni in the outermost layer of the sample are determined by Auger electron spectroscopy (AES). The surface concentrations of Co, Ni, and Fe are calculated in atomic percentages. It should be noted that the surface steel plate is cleaned for 5 to 10 minutes using a plasma sputtering device before punching to remove any contaminants (e.g., oxide layers) that may have formed on the surface of the coating.
[0082] The Fe concentration in the coating cross section is determined as follows: The annealed and alloyed steel sheet is first cleaned using a plasma sputtering device for 5-10 minutes to remove any contaminants (e.g., oxide layers) that may have formed on the coating surface. A sample approximately 10 mm wide, perpendicular to the rolling direction, is then cut from the center of the sheet and embedded in resin. The sample is then polished using 400, 800, and 2000 mesh grinders, followed by polishing with a 0.2 μm polishing solution, and finally etched with 4% nitric acid. The cross section is then analyzed using Auger electron microscopy across the coating depth to determine the Fe concentration in the cross section. The surface resistance of the coating is determined using the four-probe method. The surface of the nickel-plated steel strip, cut and flattened, is wiped with alcohol and lens paper to remove fingerprints and oil stains. The four pins of the four-probe tester are then placed in contact with the strip surface and allowed to stabilize until a reading is obtained.
[0083] Coating adhesion is measured as follows: A 0T bend is used to assess coating adhesion. The steel strip is bent 360° along an axis with a diameter equal to the specimen thickness. The folded surface is taped. If the coating does not flake off, and the bent area is examined using a SEM, good coating adhesion is indicated if the steel surface does not peel, the coating does not flake off, and no cracks are present. In Table 4, a "√" indicates good coating adhesion, and an "×" indicates poor coating adhesion (SEM images show coating flakes).
[0084] The immersion potential is determined as follows:
[0085] Immersion potential is the open circuit voltage in electrochemical testing. Electrochemical corrosion experiments on the coating surface were carried out using a three-electrode system. The corrosion solution was a 3.5wt.% NaCl solution, a saturated calomel electrode (SCE) was used as the reference electrode, and the experimental temperature was 20-25°C. The experimental sample size was 50mm×70mm as the working electrode. Before conducting the electrochemical corrosion test, all samples were cleaned with ethanol to remove oil stains on the surface. The sample was then immersed in 1.5L of 3.5wt.% NaCl solution, and the solution temperature was maintained at 25±1°C in a water bath without stirring. The electrochemical current scan rate was set to 0.02mA / min and the time was 3600s. The state of time and voltage was observed, and the open circuit voltage was taken as the open circuit voltage when it remained stable.
[0086] The electrochemical corrosion potential is determined as follows:
[0087] The electrochemical corrosion behavior was tested as follows: an electrochemical corrosion experiment on the coating surface was performed using a three-electrode system. The corrosion solution was a 3.5wt.% NaCl solution, a saturated calomel electrode (SCE) was used as the reference electrode, and the experimental temperature was 20-25°C. The experimental sample size was 50mm×70mm. Before the electrochemical corrosion test, all samples were cleaned with ethanol to remove oil from their surfaces. The sample was then immersed in 1.5L of a 3.5wt.% NaCl solution, and a water bath was used to maintain the solution temperature at 25±1°C without stirring. The corrosion potential was determined by a potentiodynamic polarization curve (Tafel), which is a curve obtained at the open circuit potential (E ocp ) is tested under the premise of stability. The test potential of the dynamic polarization curve is -200mV vs E ocp to +0.5V vsE ocp , the scanning rate is about 0.1667mV / s.
[0088]
[0089]
[0090]
[0091]
[0092] Table 4 shows that the nickel-plated steel sheet of the present invention has a first coating and a second coating on its upper and lower surfaces, respectively, with different thicknesses. The thickness of the first coating is d1 = 1.0-5.0 μm, and the thickness of the second coating is d2 = 3.0-6.0 μm. On the surface of the first coating, the mass fraction of cobalt is c1 = 0.5-5.0%; on the surface of the second coating, the mass fraction of cobalt is c2 = 1.0-10.0%. The mass fraction of Fe in the nickel-iron diffusion layer of the first coating is 5.0-30.0%; and the mass fraction of Fe in the nickel-iron diffusion layer of the second coating is 10.0-60.0%. Taking the first coating as an example, in the GDS spectrum (glow discharge spectrum), the position where the mass fraction of Ni in the nickel layer is 80% is used as the first boundary, and the position where the mass fraction of Fe in the substrate is 80% is used as the second boundary. The area between the first boundary and the second boundary is the nickel-iron diffusion layer. The nickel-iron diffusion layer in the second coating is defined similarly. The higher the mass fraction of Fe in the nickel-iron diffusion layer, the stronger the bonding force between the coating and the substrate. After the nickel-plated steel sheet of the present invention is made into a battery shell, the side with the first plating layer is used as the inner surface of the battery shell, so that when the battery is in use, the first plating layer is exposed to the electrolyte of the battery. Due to the low resistivity, high hardness, good corrosion resistance and wear resistance of nickel-cobalt alloy, the battery shell has low internal resistance and high corrosion resistance. The composition of the plating solution used when forming the plating layer in Comparative Examples 1-3 is not within the range defined by the present invention, and the bath temperature of the plating bath when forming the plating layer in Comparative Example 4 is not within the range defined by the present invention, so a plating layer with appropriate thickness and appropriate surface Co content cannot be formed. The surface of Comparative Example 5 is only nickel-plated, and its surface resistance is significantly higher than the range defined by the present invention. Its use as a battery shell steel will affect the working efficiency of the battery; the surface of Comparative Example 6 is only nickel-plated with cobalt alloy, and the bonding strength of its plating is lower than the range defined by the present invention. The plating layer is easy to fall off and the plating adhesion is poor.
[0093] It should be noted that all technical features described in the present invention can be freely combined or combined in any way unless there is a contradiction between them. Various modifications and variations can be made to the present invention without departing from the scope of the present invention, which will be apparent to those skilled in the art. For example, a feature shown or described as part of one embodiment can be used together with another embodiment to produce yet another embodiment. Therefore, the present invention is intended to cover these modifications that fall within the scope of the appended claims and their equivalents.
Claims
1. A nickel-plated steel plate, comprising a steel substrate and a first coating layer and a second coating layer respectively disposed on the upper surface and the lower surface of the steel substrate; the first coating layer and the second coating layer both comprise a nickel-iron diffusion layer, a nickel layer and a nickel-cobalt alloy layer sequentially formed on the surface of the steel substrate; in, The thickness of the first coating layer is d1=1.0-5.0 μm, the thickness of the second coating layer is d2=3.0-6.0 μm, and d2>d1; and On the surface of the first coating layer, the mass fraction of cobalt c1 = 0.5-5.0%; on the surface of the second coating layer, the mass fraction of cobalt c2 = 1.0-10.0%.
2. The nickel-plated steel sheet according to claim 1, wherein The first plating layer comprises Ni: 50.0-95.0 wt.%, Co: 0.5-10.0 wt.%, Fe: 1.0-5.0 wt.%, and the second plating layer comprises Ni: 50.0-95.0 wt.%, Co: 0.5-10.0 wt.%, Fe: 1.0-5.0 wt.%.
3. The nickel-plated steel sheet according to claim 1 or 2, wherein: The mass fraction of Fe in the nickel-iron diffusion layer of the first coating layer is 5.0-30.0%, and the mass fraction of Fe in the nickel-iron diffusion layer of the second coating layer is 10.0-60.0%.
4. The nickel-plated steel sheet according to any one of claims 1 to 2, wherein: The surface resistance of the nickel-plated steel plate is 80-120 mΩ.
5. The nickel-plated steel sheet according to any one of claims 1 to 2, wherein: When the nickel-plated steel plate is placed in a sodium chloride solution having a mass fraction of 3.5%, The immersion potential U1 of the surface of the first coating layer is -0.33 to -0.10 V, and the immersion potential U2 of the surface of the second coating layer is -0.32 to -0.10 V; and / or, The corrosion potential u1 of the surface of the first coating layer is -0.44 to -0.15 V, and the corrosion potential u2 of the surface of the second coating layer is -0.42 to -0.20 V.
6. The nickel-plated steel sheet according to any one of claims 1 to 2, wherein: The element composition of the steel matrix in mass percentage is as follows: C: 0.02-0.065%, 0<Si≤0.03%, Mn: 0.1-0.32%, 0<S≤0.01%, Cu: 0.005-0.03%, Ni: 0.005%-0.035%, Cr: 0.015-0.065%, 0<Ti≤0.002%; the balance is Fe and unavoidable impurities.
7. A battery casing formed of the nickel-plated steel sheet according to any one of claims 1 to 6, wherein: When the battery casing is in use, the first plating layer is exposed to the electrolyte of the battery.
8. A method for manufacturing the nickel-plated steel sheet according to any one of claims 1 to 6, comprising: The upper surface and the lower surface of the substrate are respectively plated with nickel and nickel-cobalt alloy in sequence to obtain a multi-layer steel strip, and then the multi-layer steel strip is continuously annealed to form the nickel-plated steel plate.
9. The method of claim 8, wherein: A Watt bath solution is used for nickel plating, and the Watt bath solution contains: 250-380 g / L nickel sulfate, 30-60 g / L nickel chloride, and 20-60 g / L boric acid; preferably, the pH of the Watt bath solution is 3.0-5.0, and the bath temperature is 40-65°C.
10. The method of claim 8, wherein: The plating solution used for nickel-cobalt alloy plating includes: nickel sulfate 200-350g / L, nickel chloride 35-60g / L, boric acid 35-45g / L, cobalt sulfate 1-20g / L and additives 0.05-0.15g / L.
11. The method of claim 8, wherein: The nickel plating current density a1 used to form the first plating layer is 1-5A / dm 2 , the current density when plating nickel-cobalt alloy is b1=3-10A / dm 2 ; The nickel plating current density a2 used to form the second coating is 3-8A / dm 2 , the current density b2 when plating nickel-cobalt alloy is 5-15A / dm 2 ; and a2>a1, b2>b1.
12. The method of claim 11, wherein: When nickel is plated, a pulse current is used with a duty cycle of 1:10-1:15; when nickel-cobalt alloy is plated, a rectangular wave pulse current is used with a duty cycle of 1:3-1:
10.
13. The method of claim 8, wherein: During continuous annealing, the annealing soaking temperature is 600-800° C., preferably 680-750° C., and the soaking time is 10-300 s, preferably 30-200 s.
